(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2021)
The evaluation of full grains per panicle is a parameter that influences the final results of the harvest in rice cultivation and is closely related to the evaluated cultivars and environmental conditions, one of which is the sowing season. The research was developed in the areas of the Jucarito Territorial Grain Research Station (ETIG), Rio Cauto municipality, Granma province, on a typical ferruginous nodular Gley soil, in a random block design with three replicas. Four cultivars IACuba-41, IACuba-30, Pearl, Bolito and lines 10375 and 10189 were studied during the cold campaigns 2018 – 2019 and spring 2019. The variable evaluated was the number of filled grain per panicle, determined by indirect calculation. It was statistically processed as a factorial variance analysis and tukey was used for a probability of 5.0% for multiple treatment comparison. The results showed that the cultivars IACuba-41 and IACuba-30 achieved the highest values, while the cultivar Bolito and the 10189 line reached the lowest values. By campaign the cold tripled to the spring one. Differentiated interaction or response was found between the cultivars and lines evaluated in relation to the two campaigns evaluated.